Prevalence of female genital mutilation and associated factors among daughters aged 0–14 years in sub-Saharan Africa: a multilevel analysis of recent demographic health surveys - Ayenew, Asteray Assmie; Mol, Ben W.; Bradford, Billie; Abeje, Gedefaw (Frontiers in Reproductive Health, 2023)
Background Female genital mutilation (FGM) is a harmful traditional practice involving the partial or total removal of external genitalia for non-medical reasons. Despite efforts to eliminate it, more than 200 million women and girls have undergone FGM, and 3 million more undergo this practice annually. Tracking the prevalence of FGM and identifying associated factors are crucial to eliminating the practice. This study aimed to determine the prevalence of FGM and associated factors among daughters aged 0–14 years. Methods The most recent Demographic Health Survey Data (DHS) datasets from sub-Saharan African countries were used for analysis. A multilevel modified Poisson regression analysis model was applied to identify factors associated with FGM. Data management and analysis were performed using STATA-17 software, and the pooled prevalence and adjusted odds ratio (AOR) with a 95% confidence interval (CI) were reported. Statistical significance was set at p ≤ 0.05. Results The study included a weighted sample of 123,362 participants. The pooled prevalence of FGM among daughters aged 0–14 years in sub-Saharan Africa was found to be 22.9% (95% CI: 16.2–29.6). The daughter's place of birth (AOR = 0.54, 95% CI: 0.48–0.62), mother's age (AOR = 1.72, 95% CI: 1.4–2.11), father's education (AOR = 0.92, 95% CI: 0.87–0.98), mother's perception about FGM (AOR = 0.42, 95% CI: 0.35–0.48), FGM as a religious requirement (AOR = 1.23, 95% CI: 1.12–1.35), mother's age at circumcision (AOR = 1.11, 95% CI: 1.01–1.23), residing in rural areas (AOR = 1.12, 95% CI: 1.05–1.19), and community literacy level (AOR = 0.90, 95% CI: 0.83–0.98) were factors associated with FGM. Conclusion The high prevalence of FGM among daughters aged 0–14 years in sub-Saharan Africa indicates the need for intensified efforts to curb this practice. Addressing the associated factors identified in this study through targeted interventions and policy implementation is crucial to eradicate FGM and protect the rights and well-being of girls.